Establishment of A Care Group in The Satya Gawa Program To Enhance The Quality of Life of People With Mental Disorders: Pembentukan Kelompok Peduli Dalam Program Satya Gawa Untuk Meningkatkan Stabilitas Orang Dengan Gangguan Jiwa - Laksono, Andi Dwi; Fatmawati, Megalia; Ardiansyah, Ahmad Nur; Nauli Harahap, Reiki (Progress In Social Development, 2022)
ABSTRACT: Mental health issues are one of the fundamental topics. Psychiatric conditions not only affect the mindset and behavior of individuals but can have an impact on the long term. The Indonesian Ministry of Health (2021) states that the prevalence of potential mental disorders in Indonesia reaches 20% of the total population. Meanwhile, in 2020, only about 58.9% of ODGJ received mental health services. Therefore, this journal article seeks to explain how the process of increasing the stability of ODGJ through the Satya Gawa Program launched by PT Indonesia Power Suralaya PGU. The research method used is qualitative with a phenomenological research approach. Data was collected by means of participant observation, interviews, documentation, and literature study. The concepts of mental health, sociopreneur, and caring groups were used to analyze the data obtained. ABSTRAK: Masalah kesehatan jiwa menjadi salah satu topik yang fundamental. Kondisi kejiwaan tidak hanya mempengaruhi pola pikir dan perilaku individu, namun dapat berdampak pada jangka panjang. Kementrian Kesehatan RI (2021) menyatakan bahwa prevalensi potensi gangguan jiwa di Indonesia mencapai 20% dari total penduduk. Sedangkan pada tahun 2020, baru sekitar 58,9% ODGJ yang mendapat pelayanan kesehatan jiwa. Oleh karena itu, artikel jurnal ini berupaya menjelaskan bagaimana proses meningkatkan stabilitas ODGJ melalui Program Satya Gawa yang dicanangkan oleh PT Indonesia Power Suralaya PGU. Metode penelitian yang digunakan adalag kualitatif dengan pendekatan phenomenological research. Pengumpulan data dilakukan dengan observasi partisipan, wawancara, dokumentasi dan studi literatur. Konsep kesehatan jiwa, sociopreneur, dan kelompok peduli digunakan untuk menganalisis data yang diperoleh.